2014
DOI: 10.1088/1367-2630/16/5/053039
|View full text |Cite
|
Sign up to set email alerts
|

Hydration layers trapped between graphene and a hydrophilic substrate

Abstract: Graphene is mechanically exfoliated on CaF 2 (111) under ambient conditions. We demonstrate the formation of a several monolayer thick hydration layer on the hydrophilic substrate and its response to annealing at temperatures up to 750 K in an ultra-high vacuum environment. Upon heating, water is released, however, it is impossible to remove the first layer. The initially homogeneous film separates into water-containing and water-free domains by two-dimensional Ostwald ripening. Upon severe heating, thick grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 54 publications
(85 reference statements)
1
60
1
Order By: Relevance
“…Presence of water layer between graphene and substrate had been noted by different authors (e.g. [17][18][19]). To our opinion, laser pulses can cause essential heating and even boiling of this water layer.…”
Section: Discussionmentioning
confidence: 76%
“…Presence of water layer between graphene and substrate had been noted by different authors (e.g. [17][18][19]). To our opinion, laser pulses can cause essential heating and even boiling of this water layer.…”
Section: Discussionmentioning
confidence: 76%
“…Beyond the thickness of approximate five layers of water, the hole doping effect is virtually saturated. Figure 11: Illustration of (a) water from the air adsorbing onto CaF2 (111) [97]. (d) The relation of free charge carrier density and surface potential difference of graphene with increasing number of confined water layers.…”
Section: Effects Of Water On the Local Electronic Properties Of Graphenementioning
confidence: 99%
“…Xu et al have demonstrated in their pioneering work 8 that water can be aggregated between a mica substrate and a graphene sheet on top. Water intercalation between graphene (cover) and mica (substrate) have recently received tremendous attention [9][10][11][12][13][14][15][16][17][18] . Such intercalated water is in contact with the environment through defects in the graphene cover, which we will further refer to as B-defects 9 .…”
mentioning
confidence: 99%